The Need for Trained Counsellors in the B.C. School - Allan, John A. B. (Canadian Journal of Counselling and Psychotherapy, 2012)
In order to assess the need for counsellors and to develop appropriate school counsellor training programmes, a questionnaire was sent to the Superintendents and Directors of the seventy-four (74) school districts in B.C. Replies were received from fifty-six (56) districts (a 76% return). The results indicated that (1)100% of the respondents believed that there was a need for trained counsellors inthe schools, (2) 86% felt there was a need for more counsellors and (3) 71%indicated that they would be willing to provide some financial help toexperienced teachers interested in counsellor training. More counsellors are needed in the elementary schools and in secondary schools outside major urban areas. Upgrading is an important priority for many secondary schoolcounsellors. The counselling skills seen as most benefiting to the schools at this time are: (a) Individual counselling, (b) Consultation with teachers and (c) Smallgroup counselling. Other key skills involve those relating to: Disciplineproblems, crisis counselling, career education and family counselling. The findings are discussed and implications are made regarding the training of school counsellors.